Effect of solar insolation on a solar kiln performance - Phonetip, Khamtan; Ian Brodie, Graham; Smith, Hilary (Souphanouvong University Journal Multidisciplinary Research and Development, 2022)
This research aimed to investigate the effect of solar insolation on the internal temperature of a solar kiln at different levels of relative humidity (RH=20%, RH=40% & RH=60%), and create mathematical modelling to simulate the solar kiln conditions. A solar kiln was installed at the National University of Laos, Faculty of Forest Science under the Department of Forest Economics and Wood Technology in June 2021, this apparatus was used in this study. The recharge and discharge model was used to predict the solar kiln temperature. The results showed that solar insolation is an important contributor to a solar kiln’s performance; however, it is not the only contributor. The solar kiln’s temperature follows a thermal recharge phase during the morning and a thermal discharge phase during the afternoon and nighttime. The set value of relative humidity and present value of relative humidity inside the solar kiln also strongly influence the solar kiln temperature. The solar kiln can provide a free source of heat up to 54ºC, this could contribute to the wood processing sector in reducing the GHG emissions through drying timber using solar kiln method, with continuous drying technique or the combination with traditional kiln which would reduce the 60% of carbon emission from a drying batch.